Challenges and Opportunities in Extending Cloud with Fog Computing - V. Raghavendran, Ch.; Anitha Patil, Dr.; Naga Satish, G.; M. Shanmukhi, Dr.; Madhuravani, B. (International Journal of Engineering and Technology, 2018)
The present â€œcloud based internet of things (IoT) frameworksâ€ are facing the challenges because of digital improvement from the â€œArtificial Intelligence, Tactile Internet, IoT, Virtual Reality, and 5G provisionsâ€. These require â€œlow latency accessâ€ that is normally attained by moving computation towards the edge of the network. One result for this is to decentralize management, applications, and information analytics into the system itself utilizing an associated and distributed approach and this model is named as â€œFog Computingâ€. The IoT sensors used to generate the data management is the main issue faced when deploying an IoT framework. Whether they correctly integrated, then cloud platforms and fog platforms might support a wide range of â€œoptimized servicesâ€. These services might be poised to take benefit of the complimentary profits in both structures. To make an integrated platform, the â€œcloud virtualization layerâ€ should increase beyond the data center to reach the â€œfog nodesâ€. To enable this expansion, a network management that helps virtualization should spread to the edges. This manuscript portrays the idea of â€œFog Computingâ€ along with challenges and its opportunities.Â Â